2013
DOI: 10.5665/sleep.2722
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects on Fast and Slow Spindle Activity, and the Sleep Slow Oscillation in Humans with Carbamazepine and Flunarizine to Antagonize Voltage-Dependent Na+ and Ca2+ Channel Activity

Abstract: Our findings indicate a differential pharmacologic response of the two types of sleep spindles and underscore a close linkage of the generating mechanisms underlying the sleep slow oscillation and the slow frontal sleep spindles for the signal transmission processes manipulated in the current study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
74
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 56 publications
9
74
0
Order By: Relevance
“…The first gradient has been well reported in the scalp literature, with a major distinction drawn between fast/parietal and slow/frontal spindles (Mölle et al, 2011; Mölle et al, 2002; Werth et al, 1997), indicating a strong agreement between the EEG literature in healthy participants and the findings in the current ECoG study in patients with epilepsy. Intriguingly, we find that the transition between fast and slow spindles seems to follow a linear pattern over the parietal and frontal regions, in agreement with previous work (Peter-Derex et al, 2012), instead of a clear dichotomy between fast and slow spindles (Andrillon et al, 2011; Ayoub et al, 2013). …”
Section: Discussionsupporting
confidence: 92%
“…The first gradient has been well reported in the scalp literature, with a major distinction drawn between fast/parietal and slow/frontal spindles (Mölle et al, 2011; Mölle et al, 2002; Werth et al, 1997), indicating a strong agreement between the EEG literature in healthy participants and the findings in the current ECoG study in patients with epilepsy. Intriguingly, we find that the transition between fast and slow spindles seems to follow a linear pattern over the parietal and frontal regions, in agreement with previous work (Peter-Derex et al, 2012), instead of a clear dichotomy between fast and slow spindles (Andrillon et al, 2011; Ayoub et al, 2013). …”
Section: Discussionsupporting
confidence: 92%
“…Can the two types be directly and selectively manipulated based on their different pharmacological profile, as indicated by studies in humans [129] and animal models [50]? Do the similarities between slow spindles and α rhythms (~8-13 Hz) in humans and primates, typical for quiet wakefulness [130], reflect common generating mechanisms and functions?…”
Section: Box 3 Outstanding Questionsmentioning
confidence: 99%
“…Therefore, it has been suggested that slow and fast spindles may reflect independent mechanisms that contribute to consolidation processing (Molle et al, 2011; Schabus et al, 2007). Furthermore, it has been demonstrated that certain pharmacological interventions can jointly increase slow-spindle activity and slow-oscillatory activity, while simultaneously decreasing fast-spindle activity (Ayoub et al, 2013). Thus, one highly speculative possibility is that by enhancing slow-oscillatory activity with SOS in elderly adults, a concomitant decrease in fast-spindle activity might be produced, but further research is necessary to assess this possibility.…”
Section: Discussionmentioning
confidence: 99%